Studies of The Impact of Warrant Financing on Corporations and The Determinants That Affect The Warrant Issues - Yeung, Chi Man (2010)
The study documents, in general, a significant positive share price response for the Hong Kong equity warrants on the announcement date of warrant issues. The result concluded that, at least upon the announcement date, is consistent with Schultz (1993) and Mayers (1998) where the market view positively to the warrant issues. The out of the money warrants further drive the result of announcement effect of the whole sample of warrants, giving a more positive and significant price response upon the announcement of warrant issues. Firms that issue the out of the money warrant ties capital inflow to favourable new related to capital needs of the company and thus consistent with Mayers (1998) sequential financing model.